Cover Image. (13th October 2021) - Vornholt, Eric; Drake, John; Mamdani, Mohammed; McMichael, Gowon; Taylor, Zachary N.; Bacanu, Silviu‐Alin; Miles, Michael F.; Vladimirov, Vladimir I.
Abstract : The cover image is based on the Original Article Identifying a novel biological mechanism for alcohol addiction associated with circRNA networks acting as potential miRNA sponges by Eric Vornholt et al., https://doi.org/10.1111/adb.13071 .